Reconstruction of Amin Abdullah's Contextual-Progressive Interpretation: Integration of Abdullah Saeed's Hermeneutics and Jasser Auda's Maqasid - Zulkarnaen Zulkarnaen; Kamaruddin Mustamin (Jurnal El-Thawalib, 2026)
Amin Abdullah adopts Abdullah Saeed’s contextual hermeneutics and Jasser Auda’s systems-based maqāṣid within the framework of integration-interconnection. However, the epistemological relationship between these two approaches has not been systematically explained. This study aims to reconstruct the relationship between Abdullah Saeed’s contextual hermeneutics and Jasser Auda’s systems-based maqāṣid in Amin Abdullah’s thought. This research is qualitative in nature and employs a library research method with an epistemological approach. Primary data were obtained from the works of Amin Abdullah, Abdullah Saeed, and Jasser Auda, while secondary data consisted of relevant books and scholarly articles. Data were collected through documentation techniques and analyzed using a descriptive-analytical method. The findings reveal that Abdullah Saeed’s contextual hermeneutics and Jasser Auda’s systems-based maqāṣid perform different yet complementary functions. Contextual hermeneutics operates at the level of textual interpretation to extract Qur’anic values, whereas systems-based maqāṣid functions at the level of operationalizing those values within complex social realities. Their relationship is complementary because they work within a continuous epistemological process. This study finds that values serve as the connecting point between textual interpretation and the operationalization of maqāṣid. Therefore, Amin Abdullah’s integration-interconnection framework can be understood as a process that moves from text to values and subsequently to the operationalization of values in contemporary social realities.